Conservation, risk aversion, and livestock insurance: The case of the snow leopard - Ted Loch‐Temzelides (Conservation Letters, 2021)
Abstract Livestock insurance consists of livestock owners pooling resources together in order to hedge against the risk of attacks by predators on their individual herds. We use an economic model to study optimal livestock insurance and to discuss its viability in improving outcomes for livestock owners. The benefit from insurance depends on the livestock owners' level of risk aversion. We calibrate the model using data from Project Snow Leopard and investigate the potential of livestock insurance for achieving conservation goals. The model predicts that leopard killings would decline under the proposed livestock insurance contract. The level of the decline depends on the degree of risk aversion. Our analysis calls for surveys that measure risk aversion of local livestock owners to be conducted in any situation where insurance is considered as a policy towards achieving conservation goals. Finally, we discuss how the proposed livestock insurance scheme could be implemented in practice.